2017
DOI: 10.1007/s00330-017-4895-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of pancreatic cancer is predictable well in advance using contrast-enhanced CT: a case–cohort study

Abstract: • Pancreatic findings in multiphasic CT help predict development of pancreatic adenocarcinoma. • Key findings are mass, inhomogeneous parenchyma and loss of fatty marbling. • Those findings were observed 34 months before confirmed diagnosis of adenocarcinoma. • Those findings were prognostic factors for pancreatic carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
7
34
0
Order By: Relevance
“…This finding, if repeated in a larger sample, could argue in favor of pancreatic fat being a predisposing condition to cancer rather than a result of malignant transformation. This notion is supported by a recent study that reported on the inhomogeneous pancreas parenchyma as a predictive factor for pancreatic carcinogenesis, long before the diagnosis and independent of the tumor site [30].…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…This finding, if repeated in a larger sample, could argue in favor of pancreatic fat being a predisposing condition to cancer rather than a result of malignant transformation. This notion is supported by a recent study that reported on the inhomogeneous pancreas parenchyma as a predictive factor for pancreatic carcinogenesis, long before the diagnosis and independent of the tumor site [30].…”
Section: Discussionsupporting
confidence: 58%
“…While accurate assessment of fatty pancreas is only possible via histopathological examination of the tissue, the accumulating evidence suggests that imaging modalities can be used to accurately estimate pancreas fat [20,[28][29][30][31]. Among the available imaging modalities, ultrasound may not be able to adequately visualize the pancreas, with fibrosis and fat both appear as hyperechogenic signals [31,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now generally accepted that the detection of small PC ≤ 10 mm including CIS is indispensable to improve the prognosis of PC. However, there are no reports regarding the characteristic CT findings in patients with small PC (≤10 mm) [ 6 , 7 , 8 , 9 , 13 , 14 , 15 , 16 , 17 ]. In this study, we attempted to identify the specific CT findings of small PC by focusing on abnormalities in MPD and pancreatic parenchyma in patients with small PC including CIS.…”
Section: Introductionmentioning
confidence: 99%